2019
DOI: 10.1177/0967391119867560
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and tensile properties of guar gum hydrogel films

Abstract: Guar gum hydrogels may be dried to form polymer films which have the potential for use as biodegradable alternatives to polymers such as low-density polyethylene. In this study, the tensile strength and tensile modulus of guar gel films having moisture contents ranging between 15% and 18% (wet basis) were measured at a strain rate of 1 mm min−1. Mean tensile strengths of the films ranged between 25 MPa and 40 MPa (dependent on composition) which is of similar magnitude to the tensile strength data for polyethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Therefore the presence of pigments (chlorophylls, carotenoids and polyphenols) could decrease the clearness of the obtained bioplastics. The strength of bioplastics produced using CH (~30,74 -39,27 MPa), SA (~17,25 -44,05 MPa) and GAL (~40,28 -79,58 MPa) in this study was similar than the reported values from different authors (25,3 MPa,22,, respectively (Galus and Lenart, 2013;Moura, et al, 2015;Jussen, et al, 2019).…”
Section: Discussionsupporting
confidence: 86%
“…Therefore the presence of pigments (chlorophylls, carotenoids and polyphenols) could decrease the clearness of the obtained bioplastics. The strength of bioplastics produced using CH (~30,74 -39,27 MPa), SA (~17,25 -44,05 MPa) and GAL (~40,28 -79,58 MPa) in this study was similar than the reported values from different authors (25,3 MPa,22,, respectively (Galus and Lenart, 2013;Moura, et al, 2015;Jussen, et al, 2019).…”
Section: Discussionsupporting
confidence: 86%
“…The increase in tensile strength with increasing gum concentration was in conformity with some previous studies of guar gum hydrogel lms and tapioca starch/ decolorized hsian-tsao leaf gum lms. 40,41 The incorporation of locust bean gum into tragacanth-based lms resulted in an improvement in the physical and mechanical properties of the lms. 25 The reinforcing effect of GT and HPMC was due to their perfect compatibility and miscibility with the alginate-aloe vera matrix as reected in the microstructure of the lms studied by SEM.…”
Section: Mechanical Properties Of the Lmsmentioning
confidence: 99%
“…In recent years, gums, as polysaccharide compounds produced from plants, seeds, and microbial resources, have been used for the development of color indicator films [74,75]. Liang et al [41] prepared an intelligent pH indicator film using the ASKG, carboxymethyl cellulose sodium, and RCA.…”
Section: Intelligent Characteristics In Natural Biopolymeric Filmsmentioning
confidence: 99%
“…The color change appeared due to the meat spoilage during the growth of microorganisms and the deterioration of samples caused by biochemical reactions. In recent years, gums, as polysaccharide compounds produced from plants, seeds, and microbial resources, have been used for the development of color indicator films [74,75]. Liang et al [41] prepared an intelligent pH indicator film using the ASKG, carboxymethyl cellulose sodium, and RCA.…”
Section: Intelligent Characteristics In Natural Biopolymeric Filmsmentioning
confidence: 99%